2018
DOI: 10.1007/s11095-018-2436-z
|View full text |Cite
|
Sign up to set email alerts
|

Chimeric Antigen Receptor T-Cells (CAR T-Cells) for Cancer Immunotherapy – Moving Target for Industry?

Abstract: The first CD19 CAR T-cell products, Kymriah and Yescarta, are entering the US market and also being evaluated for marketing authorization in the EU. This breakthrough has expanded the interest and also investments towards novel chimeric antigen receptor (CAR) designs, both for hematological malignancies and solid tumors. At the same time, there is active development in moving from autologous products to allogeneic, off-the-shelf -products. New manufacturing technologies are also emerging for production of thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
56
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(66 citation statements)
references
References 44 publications
2
56
0
2
Order By: Relevance
“…159 Overall, CARs have already resulted in remarkable achievements in a number of clinical trials, 160 and the first CAR T cell products, Yescarta and Kymriah, were recently approved by the FDA as treatments for B cell malignancies. 161 Both therapies target the CD19 protein, whose expression is selective and restricted to most B-lineage lymphocytes, while it is not expressed on normal tissues. 162 Thus, CD19 is high on the list of targets fulfilling the criteria for an immunotherapy to target antigens that are predominantly expressed on cancer cells.…”
Section: Dnam-1-based Adoptive Cell Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…159 Overall, CARs have already resulted in remarkable achievements in a number of clinical trials, 160 and the first CAR T cell products, Yescarta and Kymriah, were recently approved by the FDA as treatments for B cell malignancies. 161 Both therapies target the CD19 protein, whose expression is selective and restricted to most B-lineage lymphocytes, while it is not expressed on normal tissues. 162 Thus, CD19 is high on the list of targets fulfilling the criteria for an immunotherapy to target antigens that are predominantly expressed on cancer cells.…”
Section: Dnam-1-based Adoptive Cell Therapymentioning
confidence: 99%
“…Nevertheless, despite these promising results, one of the major drawbacks of CAR T cell therapy in general is cytokine release syndrome (CRS) caused by excessive Targeting PVR (CD155) and its receptors in anti-tumor therapy P. Kučan Brlić et al cytokine release by activated effector cells, which is potentially fatal. 161,171 Another research group analyzed the effect of DNAM-1 CAR T cells on overall health status and the amount of different cytokines in the sera of engrafted mice to investigate the drawbacks of DNAM-1 CAR T cell therapy. 172 The injection of a high dose of DNAM-1 CAR T cells indeed resulted in CRS-like responses in mice, similar to those observed in patients.…”
Section: Dnam-1-based Adoptive Cell Therapymentioning
confidence: 99%
“…For example, comparisons of CD28-to 4-1BB-based second generation CARs in CD8 + T cells, revealed that 4-1BB-based CAR T cells are more persistent and resistant to exhaustion, and express a memory-T-cell like pattern of gene expression (Long et al, 2015;Song et al, 2011) whereas CD28-based CAR T cells have a more acute anti-tumor effect (reviewed in (van der Stegen et al, 2015)). These findings led to intense research to define the optimal contexts in which to use 4-1BB-versus CD28-based CAR T cells, with both versions now in clinical use with Kymriah ® encoding CD28 and Yescarta ® 4-1BB (Salmikangas et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In the major part of the cases, these systems include retroviral or lentiviral transfection. The transferred genes delivered usually target tumor antigens, with insertion of CAR protein into the cell membrane of T cells …”
Section: Car‐t Therapymentioning
confidence: 99%